Fitness in invasive social wasps: the role of variation in viral load, immune response and paternity in predicting nest size and reproductive output. Issue 8 (27th March 2017) - Dobelmann, Jana; Loope, Kevin J.; Wilson‐Rankin, Erin; Quinn, Oliver; Baty, James W.; Gruber, Monica A. M.; Lester, Philip J.
Abstract : Within any one habitat, the relative fitness of organisms in a population can vary substantially. Social insects like the common wasp are among the most successful invasive animals, but show enormous variation in nest size and other fitness‐related traits. Some of this variation may be caused by pathogens such as viruses that can have serious consequences in social insects, which range from reduced productivity to colony death. Both individual immune responses and colony‐level traits such as genetic diversity are likely to influence effects of pathogen infections on colony fitness. Here we investigate how infections with Kashmir Bee Virus (KBV), immune response and intracolony genetic diversity (due to queen polyandry) affect nest size in the invasive common wasp Vespula vulgaris . We show that KBV is highly prevalent in wasps and expression of antiviral immune genes is significantly increased with higher viral loads across individuals. Patriline membership within a nest did not influence KBV susceptibility or immune response. A permutational MANCOVA revealed that polyandry, viral load and expression of the immune gene Dicer were significant predictors of variation in nest size. High intracolony genetic diversity due to polyandry has previously been hypothesized to improve colony‐level resistance to parasites and pathogens. Consistent with this hypothesis, we observed genetically diverse colonies to be significantly larger and to produce more queens, although this effect was not driven by the pathogen we investigated. Invasive wasps clearly suffer from pathogens and expend resources, as indicated here by elevated immune gene expression, toward reducing pathogen‐impact on colony fitness.